Novel SERPING1 gene mutations and clinical experience of type 1 hereditary angioedema from North India. Issue 3 (5th December 2020) - Jindal, Ankur K.; Rawat, Amit; Kaur, Anit; Sharma, Dhrubajyoti; Suri, Deepti; Gupta, Anju; Garg, Ravinder; Dogra, Sunil; Saikia, Biman; Minz, Ranjana W.; Singh, Surjit
Abstract: Background: There is paucity of literature on long‐term follow‐up of patients with hereditary angioedema (HAE) from developing countries. Objective: This study was carried out to analyze the clinical manifestations, laboratory features, and genetic profile of 32 patients (21 male and 11 female) from 23 families diagnosed with HAE between January 1996 and December 2019. Methods: Data were retrieved from medical records of Paediatric Immunodeficiency Clinic, Postgraduate Institute of Medical Education and Research, Chandigarh, India. Results: Median age at onset of symptoms was 6.25 years (range 1‐25 years), and median age at diagnosis was 12 years (range 2‐43 years). Serum complement C4 level was decreased in all patients. All patients had low C1‐esterase inhibitor (C1‐INH) quantitative level (type 1 HAE). SERPING1 gene sequencing could be carried out in 20 families. Of these, 11 were identified to have a pathogenic disease‐causing variant in the SERPING1 gene. While 2 of these families had a previously reported mutation, remaining 9 families had novel pathogenic variants in SERPING1 gene. Because of non‐availability of C1‐INH therapy in India, all patients were given long‐term prophylaxis (attenuated androgens or tranexamic acid (TA) or a combination of the 2). Life‐threatening episodes of laryngeal edema were managed with fresh‐frozen plasma (FPP) infusions. We recorded one disease‐related mortality in our cohort. This happened in spite of long‐term prophylaxis with stanozolol and TA. Conclusions: We report largest single‐center cohort of patients with HAE from India. Attenuated androgens, fibrinolytic agents, and FPP may be used for management of HAE in resource‐limited settings.